Numerical Simulation and Research on Flow Characteristics of Fan in the Ventilation System of Airliners - Zhao Yushu (Hangkong gongcheng jinzhan, 2019)
Fan is an important part of aircraft ventilation system, and its working condition is of an important influence on the normal operation of environmental control system. Taking a fan as the research object, under the condition of variable flow rate, the parameters of fan efficiency, pressure rise, power and so on are calculated by numerical simulation method, and the changing trend is analyzed. Combined with the limit streamline diagram and the spatial vorticity diagram, the flow field of the fan under different flow rates and the effect of different flow structures on efficiency are analyzed. The calculation and analysis show that the total pressure efficiency will increase with the increase of flow rate in a certain range, and when the flow rate reaches a certain value, the increase of flow rate will sharply reduce the efficiency. In addition, the change of flow leads to the change of static pressure on the blade surface and aerodynamic force on the fan. At low flow rate, there is a lowest point of aerodynamic force on the impeller. In a given flow range, the vortex structure in the flow field will also change with the flow, which is mainly due to the change of the angle of attack caused by the change of the flow.